BANGLADESHI MUSLIM CONSTRUCTION WORKERS IN SINGAPORE: A STUDY IN THE PROCESS OF MIGRATION AND EMPLOYMENT - Sanghita Datta (Islam Realitas: Journal of Islamic and Social Studies, 2015)
Singapore  has a long history  of receiving  labor  migrants  from all across South Asia and it has systematically  developed  a whole  range of strategies  to deal with  the shortage  of labourers  in the country.  Recent research has shown that to fulfill these shortages, large numbers of labourers are hired from Bangladesh Muslim. These labourers are temporary migrants and work in various construction sites in the country. Using field  research  (unstructured   interviews   and purposive  sampling)  as the  chief  method,  with  supporting  secondary data  from  library  research  newspaper  archives  and internet,   this  research focuses on Bangladesh's  migrant  workers  in Singapore specifically working  in the construction   sites. It will  look at what goes into the decision making or the choice of a certain  foreign   country  over  the  other  and the  role  of the  family  in the  decision  making  process.  Understanding   the process of socialization  among these  migrants  and how they  try to  bridge the gaps between  their  home  and the foreign work  place by creating a home away from  home, will  also be highlighted.   Singapura memiliki sejarah panjang menerima tenaga kerja migran dari seluruh Asia Selatan dan telah sistematis mengembangkan berbagai macam strategi untuk menghadapi kekurangan buruh di negara ini. Penelitian terbaru menunjukkan bahwa untuk memenuhi kekurangan tersebut, sejumlah besar buruh dipekerjakan dari Bangladesh Muslim. Para buruh ini merupakan migran sementara dan mereka bekerja di berbagai konstruksi di negara ini. Dengan menggunakan penelitian lapangan (wawancara terstruktur dan purposive sampling) sebagai metode utama, dengan didukung oleh data sekunder dari perpustakaan, arsip, koran, penelitian, dan internet, penelitian ini berfokus pada pekerja migran Bangladesh di Singapura secara khusus bekerja di lokasi konstruksi. Penelitian ini akan melihat apa yang terjadi dalam pengambilan keputusan atau pilihan dari negara asing tertentu atas yang lain dan peran keluarga dalam proses pengambilan keputusan. Memahami proses sosialisasi di antara para migran dan bagaimana mereka mencoba untuk menjembatani kesenjangan antara keluarga dan tempat kerja asing dengan menciptakan suasana seperti dirumah sendiri meskipun mereka jauh dari rumah juga akan disorot.